Matriculation students’ usages and its driving factors in mobile learning for Chemistry - Wai Foong Lok; Mahizer Hamzah (International Journal of Evaluation and Research in Education (IJERE), 2022)
The study identified how Malaysian matriculation students employ mobile devices for learning Chemistry, and the driving factors that influence their use of mobile devices for learning Chemistry. A qualitative case study approach was adopted in this study, in which interviews and student journals were the main instruments used for the data collection process. The study was conducted in a matriculation college, and all students were invited to participate in the study voluntarily. A total of 17 students who were actively using mobile devices to learn Chemistry were selected for individual and face-to-face interviews. The data were analyzed in a three-stage process to inductively identify the themes. The analysis revealed that matriculation students used mobile devices for referential and collaborative learning activities. They preferred to search the relevant learning resources on the web, and learn collaboratively with their peers or lecturers. Meanwhile, the driving factors of these mobile learning practices were primarily due the ability of mobile learning to overcome their learning difficulties, convenience, as well as the ability to provide a better user experience in the digital age. The findings of this study suggest that the mobile device is a viable social constructivism pedagogical tool for learning Chemistry. The lecturers and management of matriculation colleges can use the findings of this study as a basis to promote the adoption of mobile learning for Chemistry in the digital age.